Students’ learning experience and preferences: a case of Malaysian university students - Rini Suryati Sulong; Nurhamiza Mumin @ Osman (Centre for Academic Excellence and Development (CAED), UMS, 2023)
In just a few years, Malaysia’s education landscape has transformed the application of online learning from a novelty into a necessity. In the case of Universiti Malaysia Sabah (UMS), the adoption of the National e-Learning Policy means that all lecturers must have teaching and learning materials in the form of e-learning. For the majority of university students in the country, the concept of e-learning is part and parcel of a student’s university learning experience. The purpose of this study was to explore the learning experience from the students’ perspective. A total of 190 students answered questions to assess their e-learning experience in UMS and to gather information on their preferred mode of study. Our results show that a large majority of the students had a positive experience towards the use of online learning in their university courses. It was also found that the majority of students preferred a blended learning format that allowed for both face-to-face and online learning experience. We believe that the results of this study can help increase our understanding of the reasons for students’ learning preferences, which in turn can help lecturers develop a more fitting and conducive teaching and learning materials that can translate to an enjoyable student learning experience.